THE HISTORY OF SOGDAAND SOGDIANS IN THE WORKS OF ACADEMICIAN YU. F. BURYAKOV - Ваисова Н. А. (TARIXIY TADQIQOTLAR, 2025)
The article is dedicated to an outstanding scientist, academician, and archaeologist, Yuri Fedorovich Burakov, who was a graduate of the Historical Faculty of the Mirzo Ulugbek National University of Uzbekistan. In different periods of his life, he worked at the Faculty of History, in particular, from 1999 until his death. The article, along with the main facts of his life and work, pedagogical work, examines an important milestone in his research work - the study of the history of the Great Silk Road, in general, the Sogdians and Sogd, in particular. An attempt is made to assess the role of Sogdians as diplomats and merchants on the Great Silk Road in the life of Turkic and Chinese society.